2021
DOI: 10.2337/dbi20-0033
|View full text |Cite
|
Sign up to set email alerts
|

Living Dangerously: Protective and Harmful ER Stress Responses in Pancreatic β-Cells

Abstract: Type 2 diabetes (T2D) is a growing cause of poor health, psychosocial burden, and economic costs worldwide. The pancreatic β-cell is a cornerstone of metabolic physiology. Insulin deficiency leads to hyperglycemia, which was fatal before the availability of therapeutic insulins; even partial deficiency of insulin leads to diabetes in the context of insulin resistance. Comprising only an estimated 1 g or <1/500th of a percent of the human body mass, pancreatic β-cells of the islets of Langerhans are a vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 90 publications
3
48
0
Order By: Relevance
“…Based on these observations, we hypothesized that the capacity of islet cells to respond and adapt to ER stress might be deficient in the absence of γ-carboxylation, potentially leading to impaired β-cell function. In support of this notion, we found that a network of genes previously implicated in the β-cell response to ER stress, including Ddit3 (CHOP), Atf4 , Eif2ak3 (PERK) , Herpud1 , Trib3 , Pdia4 , Ppp1r1a and Atp2a2 (SERCA2) (Johnson et al, 2014; Sharma et al, 2021), was down-regulated in absence of γ-carboxylation (Fig. 1D).…”
Section: Resultssupporting
confidence: 70%
“…Based on these observations, we hypothesized that the capacity of islet cells to respond and adapt to ER stress might be deficient in the absence of γ-carboxylation, potentially leading to impaired β-cell function. In support of this notion, we found that a network of genes previously implicated in the β-cell response to ER stress, including Ddit3 (CHOP), Atf4 , Eif2ak3 (PERK) , Herpud1 , Trib3 , Pdia4 , Ppp1r1a and Atp2a2 (SERCA2) (Johnson et al, 2014; Sharma et al, 2021), was down-regulated in absence of γ-carboxylation (Fig. 1D).…”
Section: Resultssupporting
confidence: 70%
“…Collectively, the primary function of the ER stress response program is to sense client protein overload through the loss of available chaperone protein binding (i.e., accumulation of misfolded proteins) and adjust ER folding capacity via the activation of transcriptional and translational programs that modulate the expression of ER chaperones, PDIs, and glycosylation enzymes [ 100 , 106 , 111 ]. A detailed discussion of the contribution of these sensors to β-cell function and their transcriptional programs is beyond the scope of this review and was expertly reviewed elsewhere [ 99 , 112 ].…”
Section: Nutrient Sensing Of Client Protein Load In the Ermentioning
confidence: 99%
“…Given the prolonged protein synthesis repression in males following ER stress, we next quantified cell death, another ER stress-associated phenotype ( 80 ), in male and female islets. Using a kinetic cell death analysis, we observed no significant increase in apoptosis in female islet cells with 0.1 μM or 1.0 μM Tg treatment compared with controls after 84-hours (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests sex differences in ER stress-associated phenotypes occur prior to male-female differences in peripheral insulin sensitivity. Indeed, islets isolated from males and females with equivalent sensitivity also show a sex difference in protein synthesis repression, a classical ER stress-associated phenotype ( 80 ). While estrogen affects insulin biosynthesis via ERα ( 49 ), future studies will need to determine whether estrogen contributes to the ability of female islets to restore protein synthesis to basal levels faster than male islets following ER stress.…”
Section: Discussionmentioning
confidence: 99%